Omega-3 Fatty Acid Based Nanolipid Formulation of Atorvastatin for Treating Hyperlipidemia - Sreedhar, Revathy (Adv Pharm Bull, 2019)
Purpose: In the current study, attempts have been made to formulate an omega-3 fatty acid based nanostructured lipid carriers of atorvastatin (AT), for treating hyperlipidemia; and to evaluate their antihyperlipidemic activity using in vitro and in vivo studies. Methods: Omega-3 fatty acid based AT-loaded nanolipid carriers (NLC) were formulated by the melt emulsification ultrasonication technology. The prepared NLC consist of stearic acid (as solid lipid), omega-3 fatty acid (as liquid lipid), Tween 80, poloxamer 188 (surfactants) and soya-lecithin (co-surfactant). Results: AT loaded NLCs have a particle size of 74.76 ± 4.266 nm, a zeta potential value of -36.03 ± 1.504 mV and a high drug entrapment efficiency (EE) of 86.70 % ± 0.155. The release of AT from NLCs exhibited a sustained behaviour, which made it an ideal vehicle for drug delivery. MTT assay results indicated that NLCs are compatible with L929 (mouse fibroblast) cell lines. Anti-hyperlipidemic study showed a significant reduction in LDL and TG levels in serum with the orally administered Omega-3 fatty acid based AT loaded NLCs when compared to marketed formulation. Conclusion: The results demonstrated that the omega-3 fatty acid based NLC has the potential to be a promising nanomedicine for the treatment of hyperlipidemia.